Living with Atrial Fibrillation: An Analysis of Patients' Perspectives - Meral Altiok, PhD; Mualla Yilmaz, PhD; Ibrahim Rencüsoğullari, MD (Elsevier, 2015)
Purpose: The aim of this study was to determine the perceptions of patients with atrial fibrillation regarding the disease, to reveal their feelings, thoughts and wishes, and to investigate their perspectives and coping behaviors towards their condition. Methods: Phenomenological methodology was used. The study population consisted of a total of 225 patients treated by the cardiology department of a university hospital, while the study sample consisted of 32 patients who met the inclusion criteria. A semistructured interview addressed perceptions of patients with atrial fibrillation regarding the disease. Data were collected by asking the participants the three questions on the In-depth Individual Interview Form. Data were analyzed using the continuous comparative method of Colaizzi. Results: In the study sample, 50.0% of participants were female, 69.0% were married, and the mean age was 66.90 years (± 7.90 years). As a result of the content analysis, four main themes and 15 subthemes were identified: patient's mental status regarding the disease, patient's social status regarding the disease, patient's physical condition regarding the disease, and disease management and coping with the disease. The study found that individuals with atrial fibrillation faced major limitations in their daily living activities and social lives due to the disease symptoms and warfarin use. Conclusions: Patients need to be provided with relevant individual training and counselling so that they lead more satisfactory lives. In addition, appropriate health appointment and monitoring systems should be developed for patients to reduce the problems associated with frequent follow-up appointments.